Connected in freedom? Reconstructing a foundational value in EU and US foreign policy discourses - Ville Sinkkonen; Henri Vogt (Springer, 2026)
The ideal of freedom has historically instituted the Transatlantic Community of Val-
ues spanning the USA and Europe. Given the framework of liberal crises that cur-
rently dominates Western mental maps, it is crucial to contemplate what has hap-
pened to this legacy of freedom and, consequently, to the very foundations of this
value community. To achieve this, we draw on the theoretical debates on freedom to
construct a novel conceptual framework of the potential uses of the notion in politi-
cal discourses. This scaffold is then utilised as a tool to analyse, and ultimately com-
pare, the employment of freedom in a selection of documents produced by the lead-
erships of the EU and the USA since the turn of the millennium.